Correcting the frenal pull and increasing the width of keratinized mucosa around endosseous implants using denudation procedure - Park Jun-Beom (Wolters Kluwer Medknow Publications, 2008)
The frenum exerts a pull upon the tissue and can lead to the continuation of the lesion, and the keratinized tissue provides increased resistance to the periodontium. Various techniques have been used to deepen the vestibule and increase the keratinized mucosa. However, there is no case report on correcting the frenal pull and increasing the keratinized mucosa around dental implant using denudation procedure. This article presents a case of frenal pull that was corrected with denudation procedure with the incision line within the keratinized tissue.